Sol-Gel Synthesis of Monodisperse Silica Globules and Optical Properties of Ordered and Disordered Materials Based on Them - N. V. Gaponenko; S. M. Kleshcheva; E. I. Lashkovskaya; V. A. Labunov; I. L. Martynov; A. A. Chistyakov; N. I. Kargin; T. F. Raichenok; L. V. Sudnik; A. R. Luchаnok; M. Wang (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Monodisperse silica globules of about 250–300 nm in size have been synthesized by the sol-gel method. These globules form the basis for the synthesis of artificial opals – three-dimensional photonic crystals and disordered opal matrices. Matte coatings on quartz glass consisting of monodisperse silica globules and barium titanate xerogel doped with erbium and ytterbium, demonstrating up-conversion luminescence of erbium, have been synthesized. A change in the photonic band gap caused by heat treatment in the reflectance spectra of synthetic opals containing barium titanate xerogel and residues of ethylene glycol not removed by heat treatment has been shown.